Raw data for best practice study on sustainable insect-based shrimp feeds - Wilke, Thomas; Barth, Annalena; Justus Liebig University Giessen (My University, 2024)
The dataset contains the results of a literature search to identify contributing parameters that may affect life-history parameters of shrimp fed with black soldier fly meal or larvae and the raw data for a best-practice study to assess the effects of black soldier fly feed on life-history and physiological traits of the Pacific white shrimp. The dataset contains five sheets: 1. Summary of 16 publications investigating the use of the black soldier fly as a protein substitute for fishmeal in Pacific white shrimp, 2. Raw data for the controlled trial investigating the effects of fishmeal (FM) and black soldier fly (BSF) based feeds on life-history and physiological traits of Pacific white shrimp, 3. Raw data for an experiment investigating the effects of fishmeal- (FM) and black soldier fly (BSF) based feeds on the contents 18 amino acids (ALA, ARG, ASP, CYS, GLU, GLY, HIS, ILE, LEU, LYS, MET, PHE, PRO, SER, THR, TRP, TYR and VAL) in % dry matter of individual Pacific white shrimp (PWS), 4. Raw data for an experiment investigating the proximate compositions of fishmeal- (FM) based compound feed and black soldier fly (BSF) larvae (DM = dry matter), 5. Raw data for an experiment investigating contents of 18 amino acids (in % dry matter) of a fishmeal- (FM) based diet and black soldier fly (BSF) larvae (DM = dry matter).
Keywords: Aquaculture; ddc:570